Wykluczenie społeczne a zrównoważony rozwój - podstawowe relacje przyczynowo-skutkowe - Borys, Tadeusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article emphasizes the theoretical and practical significance of recognizing relations between social exclusion and the paradigm of sustainable development. Social exclusion poses a direct threat undermining social order. Having explained the concept of social exclusion and the related categories of integration and social cohesion, the article suggests the outline of indicator analysis related to social exclusion and integration in a cause-effect system, incorporating the concept of sustainable development. The performed substantial presentation of cause-effect sequence may be used in constructing the monitoring system of these social phenomena. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (7); 2007; nr 1185, s. 30-40